Pengembangan Kreativitas Siswa-I Sekolah Dasar 060830 Medan Melalui Kegiatan Lomba Menggambar dan Mewarnai Memperingati Hari Pendidikan Nasional Tahun 2023 - Jordan Joel Hiroshi Pinem; Malida Putri (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
In USU partner MBKM activities, it is necessary to have one form of program to be implemented in schools. This activity was chosen so that students can express the results of their imagination. So they can make creativity such as drawing and coloring which makes them happy and happy in the atmosphere of everyday formal learning activities. This activity also trains students so they can have creativity in drawing and coloring to give colors that match the image object. This activity is expected to improve students' ability to concentrate in carrying out future assignments. This activity was carried out to welcome the commemoration of National Education Day 2023.